(untitled) (Texas Journal of Philology, Culture and History, 2022)
Montage has grown remarkably with the evolution of cinema and the productive machinery. It has achieved a steady turn in the construction of cinematic and television work and the role of parallel montage in creating a distinctive and exciting film structure that motivates the two researchers to focus on the film rhythm or rhythm in dramatic work, specifically in the contemporary television series, which we see is often in a new kind of TV drama with intensity. The montage and its significant role in dramatic construction have formed an advanced level for filmmakers and television series in terms of creating distinctive and exciting works, Since the rhythm contributes a variety of relationships between elements of the cinematographic medium via image or sound "There was a keen desire to build it with a renewed perspective, whether by designing the view to build rhythm or montage or through the montage that broke into every part of the work or through any other process in the medium, The two researchers see that the film in general creates the rhythm with a lot of elements of the film’s language. such as lighting, scenery, actor, music, photography or sequence of events via scriptwriting, as well as the view that montage often decides the entire work in montage rooms, and with high-tech renewable shows that the "Parallel Montage" parallel montage "Action Parallel" He is engaged in creating tension and suspense in the recipient by building exciting and dazzling scenes, hence the researchers have built their scientific hypothesis according to the following title: - Parallel synthesis and rhythm structure in the television series - analytical study in contemporary works. The research may be of four chapters. The first was the methodological and second framework of the theoretical framework. The third was for research procedures. The quarter included analysis, findings, conclusions, recommendations and proposals, and then a summary in English .